Localization of phosphatidylinositol signaling components in rat taste cells: role in bitter taste transduction. - Hwang, P M (1990)
To assess the role of phosphatidylinositol turnover in taste transduction we have visualized, in rat tongue, ATP-dependent endoplasmic reticular accumulation of 45Ca2+, inositol 1,4,5-trisphosphate receptor binding sites, and phosphatidylinositol turnover monitored by autoradiography of [3H]cytidine diphosphate diacylglycerol formed from [3H]cytidine. Accumulated 45Ca2+, inositol 1,4,5-trisphosphate receptors, and phosphatidylinositol turnover are selectively localized to apical areas of the taste buds of circumvallate papillae, which are associated with bitter taste. Further evidence for a role of phosphatidylinositol turnover in bitter taste is our observation of a rapid, selective increase in mass levels of inositol 1,4,5-trisphosphate elicited by low concentrations of denatonium, a potently bitter tastant.